Kajian Level Of Service Kereta Rel Listrik (KRL) Dan Kereta Rel Diesel (KRD) Ekonomi Jabodetabek - Purwoko, Purwoko (Sekretariat Badan Penelitian dan Pengembangan Perhubungan, 2010)
Many effort that PT. KA (Persero) have done to incrase the services for many customer from trainuser. Without fail with Jabodetabek commuter train. To know about satisfaction level of KRL andKRD ]abodetabek Economic, citizen's apinian that hook be another with readinesss t.o necessity ofcitizen or expectation of citizen as a train services user.An inferior lerel services is because the supply readiness with demand isn't balance, especially at hours. In normal condition it isn't the problem to face lnj prepare services, but many variable ofproblems that must have a special handing. It means, bout services reddiness that give many statisfactionfor many custo1ner with important expectation.Relation between readiness and necessity, to decide where is their wetness part in lerel of services. So,to incrase the KRL and Jabodetabek Economic KRD if wee see from weakness part it needs a newarrangement which fulfih with train standard services big city, to hook one anather with services gapof citizen expectation in this moment.Key words : Level of Services